ANALISIS PENINGKATAN PENGETAHUAN DAN KESADARAN MASYARAKAT DUSUN KRANDAN KEBONREJO DALAM PENGELOLAAN LIMBAH UNTUK KESEHATAN MELALUI PELATIHAN EKOENZIM - Laila Septiana, Uma; Fitriana, Vita; Nugroho, Galih (Jendela Inovasi Daerah, 2024)
Ecoenzymes are an effort to overcome the problem of managing society's organic waste. This method has been implemented in several areas, one of which is Kebonrejo Village. It is hoped that the distribution of ecoenzymes throughout society can reduce the amount of household waste that is not managed properly and increase community participation in maintaining environmental cleanliness. The ecoenzyme socialization and training program carried out in the context of Real Work Lectures (KKN) in Krandan Hamlet aims to increase public knowledge and awareness regarding organic waste management through an ecoenzyme socialization program among housewives in Kebonrejo Village. The implementation method was carried out by interviewing randomly selected housewives to understand their knowledge and awareness about waste management and ecoenzymes. Furthermore, socialization and practical training for ecoenzyme production were held with selected housewives. The analysis technique used is qualitative analysis, where the results of interviews conducted randomly with housewives are analyzed to develop appropriate outreach materials based on the needs and understanding of housewives. This program involves the community and aims to overcome the issue of managing organic waste which was previously disposed of by mixing it with other waste, then conveying knowledge and awareness to the community through ecoenzyme outreach. The results of this program show an increase in housewives' knowledge and awareness regarding waste management and the benefits of ecoenzymes by seeing their enthusiasm. It can be concluded that this program has succeeded in increasing the knowledge and awareness of housewives, which has led to positive impacts on waste management and environmental conservation.